Utilization of Interactive Learning Multimedia for Arabic Language Teachers in Madrasah Tsanawiyah (MTs) Cirebon City - Sumiarni, Nanin; Masri’ah; Laely, Nelly Husni; Kusnawati, Yanti (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
Technological advances, as contained in learning multimedia, must be accompanied by teacher competence in innovating and utilizing learning media in the classroom. The role of learning multimedia is very important to support the learning process. Interactive learning multimedia is a combination of media that aims to make it easier for teachers to convey learning material. However, teaching and learning activities in schools have not carried out conventional learning and used effective, efficient and easy learning media. The present study discusses the Utilization of Interactive Learning Multimedia for Arabic Language Teachers at Madrasah Tsanawiyah (MTs) in Cirebon City. The purpose of this community service is to increase the knowledge of Arabic language teachers in MTs-Kota Cirebon about the concept of Canva, Quiziz, and PPTx learning media, and to improve the skills of teachers in MTs-Kota Cirebon to create these learning media. The service method used is Service Learning (SL), which is an activity that involves practical experience, academic learning and community involvement. The results of the Community Service activities showed that service activities had an impact on participants by increasing the knowledge of teachers at MTs about the concepts of Canva, Quiziz, and PPTx learning media. As well as being able to develop these learning media so as to produce audio-visual teaching material products using Powerpoint Show, Canva and Quiziz which were compiled based on the service and training modules.